The Dynamics of Understanding and Rejecting Hadith as a Source of Islamic Law: A Study of Inkar al-Sunnah and Syiah - Fazar Ramadhan; Nurjaya; Sumarta Sumarta; Kusyana Kusyana; Rifqi Rifqi (Penerbit Hellow Pustaka, 2025)
This study aims to examine the meaning of hadith as one of the primary sources of Islamic law. The research employs a literature study design, with data collection conducted through the review of scholarly journals, reference books, and publications relevant to the theme of Islamic legal sources, particularly hadith. The main findings indicate that hadith (or sunnah) encompasses all sayings, actions, and approvals attributed to Prophet Muhammad (peace be upon him), serving as essential guidance for human well-being alongside the Qur’an. However, the development and transmission of hadith have not been as straightforward as that of the Qur’an. Various doubts and even rejections have emerged alongside the evolution of hadith studies. Skepticism toward hadith reached a peak with the emergence of groups that deny the authority of the sunnah (Inkar al-Sunnah), including certain interpretations within Shia Islam that are often viewed as deviating from the perceived authenticity of Prophetic traditions. The implications of this study highlight the importance of enhancing public understanding of hadith in everyday life, enabling Muslims to apply Islamic teachings more effectively. The originality of this research lies in its comprehensive analysis of the dynamics of acceptance and rejection of hadith, particularly through the lens of Inkar al-Sunnah and Shia Islam perspectives, which are often underexplored in mainstream discussions on the authenticity of Islamic legal sources.